2002
DOI: 10.1016/s1010-7940(02)00594-8
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-assisted suction drainage versus conventional treatment in the management of poststernotomy osteomyelitis

Abstract: We conclude from our experience in the treatment of 42 patients with poststernotomy osteomyelitis that VASD shortened wound healing and hospital stay and thus proved to be an excellent alternative to conventional open management of these wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 15 publications
1
42
1
9
Order By: Relevance
“…913,914,973 Although several studies have suggested that vacuumassisted closure therapy can be a successful alternative to conventional standard therapy, [913][914][915][916][917][918][919][920][921]973 the data are from single-center retrospective studies of patients with heterogeneous disease processes. As a result, it seems reasonable to suggest that both conventional and vacuum-assisted closure therapy can be used in the treatment of mediastinitis.…”
Section: Postoperative Cognitive Impairmentmentioning
confidence: 99%
“…913,914,973 Although several studies have suggested that vacuumassisted closure therapy can be a successful alternative to conventional standard therapy, [913][914][915][916][917][918][919][920][921]973 the data are from single-center retrospective studies of patients with heterogeneous disease processes. As a result, it seems reasonable to suggest that both conventional and vacuum-assisted closure therapy can be used in the treatment of mediastinitis.…”
Section: Postoperative Cognitive Impairmentmentioning
confidence: 99%
“…Wound closure (secondary healing or surgical closure) was described as the incidence of complete wound closure in 2 studies 20,22 and as the time to wound closure (complete or incomplete) in 7 studies 23,[26][27][28]31,36,37 (Table 3). Only 2 of the 5 RCTs 20,26 and 2 of the 4 non-RCTs 28,37 reported a significant advantage in favor of NPWT.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Of the remaining studies, 7 (reported in 8 articles) were RCTs [20][21][22][23][24][25][26][27] and 10 were non-RCTs. [28][29][30][31][32][33][34][35][36][37] According to information from study registries, authors of publications, and the manufacturer (KCI), a further 19 trials were currently ongoing (n = 7), completed but not published (n = 3), or prematurely terminated (n=5); the status of 4 trials was unknown 38 ( Table 1). Reasons for premature termination of trials included slow enrollment, high attrition rates, changes in clinical practice, and design flaws (KCI, written communication, August 19,2005); none of the results of these 5 trials have been published to date.…”
Section: Literature Searchmentioning
confidence: 99%
“…Growing experience with VAC treatment in the fi eld of cardiac surgery is showing its over the conventional treatment of sternal infections including either one-step surgical debridement, sternal rewiring and closed mediastinal drainage or repeated debridement, open packing and subsequent sternal reconstruction 8-11, 16, 17 . In the VAC group, freedom from mediastinal microbiological cultures was achieved earlier, C-reactive protein level declined more rapidly, in-hospital stay was shorter, sternal closure was achieved earlier and long-term survival tended to be higher [17][18][19][20] . VAC therapy markedly reduced required surgical intervention and reoperations for persistent infections, even in the group of high-risk patients 19 .…”
Section: Discussionmentioning
confidence: 96%